Effect of Various Ions, pH, and Osmotic Pressure on Oxidation of Elemental Sulfur by Thiobacillus thiooxidans - Suzuki, Isamu (American Society for Microbiology, 1999)
The oxidation of elemental sulfur by Thiobacillus thiooxidans was studied at pH 2.3, 4.5, and 7.0 in the presence of different concentrations of various anions (sulfate, phosphate, chloride, nitrate, and fluoride) and cations (potassium, sodium, lithium, rubidium, and cesium). The results agree with the expected response of this acidophilic bacterium to charge neutralization of colloids by ions, pH-dependent membrane permeability of ions, and osmotic pressure.